Em direção a uma reflexão conceitual para elaboração de uma gamificação na perspectiva sociointeracionista - Honorato, Agda Isabele Gonsalves (2021)
This article aims to build the concept of Gamification from a socio-interactionist perspective. Essential aspects of Gamification will be discussed in the construction of a pedagogical proposal centered on the debate and the construction of knowledge in the Zone of Proximal Development. To this end, it discusses aspects highlighted by technology in the way access to information and knowledge has taken place in contemporary society, reflecting on its role in education to promote learning that seeks the integration between education, technologies and society. Identifies and punctuates a brief discussion about the concept of gamification in general aspects and in the educational field. Therefore, it characterizes gamification, when based on sociointeractionism, as a possible approach to promote learning in the educational scenario, with the potential to promote the integration between education, technologies and contemporary society.